A Phenomenological Account of School Education. Learning Experience as an Opportunity for the Integral Formation of Individuality - Bianca Bellini; Carmelo Galioto (University of Bologna, 2022)
What importance do we recognize to the relationship between education and individuality in today's educational institutions? Recent educational policy choices are increasingly focused on proposing curricula based on the skills to be acquired, (standard) action parameters for schools and on the use of "accountability" devices aimed at verifying the achievement of expected results. Following a similar approach, the individuality of each appears as a neglected element. In this article, the link between education and individuality in school curricula is addressed, according to a phenomenological perspective. The starting point outlines a synthetic picture of the ways in which the philosophy of contemporary education thematizes the issue; then, in a second part, it develops a phenomenological description of the relationship between education and individuality such as to integrate and broaden the contributions of today's philosophy of education. The article concludes by showing some implications aimed at rethinking the school experience as an opportunity for integral education and suggests indications for possible further research.